To find the solution of the system of equations given by:
- \( y = -2x + 8 \)
- \( y = 4x - 10 \)
we can solve for \( x \) by setting the two right-hand sides equal to each other since both expressions equal \( y \):
\[ -2x + 8 = 4x - 10 \]
Now, let's solve for \( x \):
- Add \( 2x \) to both sides:
\[ 8 = 6x - 10 \]
- Add \( 10 \) to both sides:
\[ 18 = 6x \]
- Divide both sides by \( 6 \):
\[ x = 3 \]
Next, we can substitute \( x = 3 \) back into either equation to find \( y \). We'll use the first equation:
\[ y = -2(3) + 8 \]
Calculating this gives:
\[ y = -6 + 8 = 2 \]
Thus, the solution of the system of equations is:
\[ \text{The solution of the system of equations is } (3, 2). \]